(untitled) (International relations and international law Journal, 2019)
Abstract. Since the accession to power of the fifth generation of rulers headed by Chinese President Xi Jinping, serious changes have taken place in the principle of foreign policy of the People’s Republic of China. The principle “not to be a leader in international relations, be in shadow” which had been strictly observed of Mao Zedong and Ding Xiaoping, was given to oblivion. China has transferred to new principles, now it is ready to assume responsibility in solving the common human problems on the global level sticking to the motto of mutually beneficial peace and politics in order to become “the leader” in their settlement. These changes are vividly seen in the Chinese “Belt and Road” initiative, rejuvenation of “the Chinese dream” and the initiative of “the common destiny of mankind” which have become the motto of foreign policy of Xi Jinping. At any meeting or summit of the global level (bilateral, multilateral, at the sessions of regional and international organizations), Xi Jinping is constantly bringing up the issue of “the common destiny of mankind”. Due to the fact that they do not manifest any visible expansionistic or empirical sings, they gain more supporters of their initiatives by their attractive proposals in tackling such global problems as international terrorism, global warming, ecology, etc. The article analyses the principles of foreign policy of People’s Republic of China by studying the we initiatives focusing on its merits and demerits, advantages and threats to other states. Key words: The People’s Republic of China, Xi Jinping, Chinese foreign policy, “The common destiny of mankind”, “Chinese dream”.